Benefit evaluation of power grid project based on matter-element extension model. Issue 1 (February 2021) - Ye, Qiang; Xu, Weiting; Chen, Bo; Wang, Siqi; Wu, Haoyu
Abstract: Under the background of power market reform, power grid enterprises should continue to expand new business and new mode. Based on the background of power reform, this paper constructs the power grid evaluation index system considering the economic, technical and social aspects, and uses the variable weight theory to determine the weight of each index. The matter-element extension comprehensive evaluation model based on the ideal interval method is used to evaluate the benefits of power grid projects. It lays a theoretical foundation for the formulation of marketing strategy and the promotion of economic benefits of power grid company.